1995
DOI: 10.1073/pnas.92.24.11175
|View full text |Cite
|
Sign up to set email alerts
|

Calcium/calmodulin-dependent kinase II and long-term potentiation enhance synaptic transmission by the same mechanism.

Abstract: Ca2+-sensitive kinases are thought to play a role in long-term potentiation (LTP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
227
0
6

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(250 citation statements)
references
References 33 publications
14
227
0
6
Order By: Relevance
“…The authors attributed this change to a shift toward reduced cortical excitability and an enhanced inhibitory drive in the model of Rett syndrome, rather than to any intrinsic anomaly in the neurons themselves. 125 Ca þ 2 /calmodulin-dependent protein kinase II (CaMKII) is an important mediator of LTP [126][127][128][129][130] and other forms of synaptic plasticity. 131 Stimuli that induce LTP also persistently activate CaMKII, which may be critical for the molecular memory of synaptic events.…”
Section: Mouse Models Of Genetic Clinical Disorders With Autism Symptmentioning
confidence: 99%
“…The authors attributed this change to a shift toward reduced cortical excitability and an enhanced inhibitory drive in the model of Rett syndrome, rather than to any intrinsic anomaly in the neurons themselves. 125 Ca þ 2 /calmodulin-dependent protein kinase II (CaMKII) is an important mediator of LTP [126][127][128][129][130] and other forms of synaptic plasticity. 131 Stimuli that induce LTP also persistently activate CaMKII, which may be critical for the molecular memory of synaptic events.…”
Section: Mouse Models Of Genetic Clinical Disorders With Autism Symptmentioning
confidence: 99%
“…In particular, this kinase is widely believed to be a critical mediator of long term potentiation (LTP), a cellular mechanism that is thought to underlie learning and memory (Bliss and Collingridge, 1993). Several studies have demonstrated that CaMKII is necessary for the induction of LTP (Malinow et al, 1989;Malenka et al, 1989;Silva et al, 1992;Giese et al, 1998), and that introduction of activated CaMKII is sufficient to potentiate synaptic responses in neurons (Pettit et al, 1994;Lledo et al, 1995;McGlade-McCulloh et al, 1993). CaMKII is enriched at the postsynaptic density (PSD) (Kennedy et al, 1983;Suzuki et al, 1994;Petersen et al, 2003), a protein-dense specialization at the post-synaptic membrane that is composed primarily of scaffolding proteins, ion channels, and signal transduction enzymes (Ziff, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…CaMKII␣ knockout mice show impaired hippocampal long term potentiation, a cellular model for learning and memory (12). Conversely, introduction of CaMKII␣ into neurons augments postsynaptic responses and occludes further electrically induced long term potentiation (13,14).CaMKII␣ undergoes calcium/calmodulin-dependent autophosphorylation on Thr 286 in its regulatory domain, rendering the kinase partially calcium-independent (1, 2). This reaction has been proposed as a "molecular switch," translating transient calcium elevation into prolonged kinase activity (15, 16), which becomes subject to regulation by protein phosphatases.…”
mentioning
confidence: 99%
“…CaMKII␣ knockout mice show impaired hippocampal long term potentiation, a cellular model for learning and memory (12). Conversely, introduction of CaMKII␣ into neurons augments postsynaptic responses and occludes further electrically induced long term potentiation (13,14).…”
mentioning
confidence: 99%